2017
DOI: 10.1371/journal.pone.0181032
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and perceived stigma towards tuberculosis among pastoralists; Do they differ from sedentary communities? A comparative cross-sectional study

Abstract: BackgroundEthiopia is ninth among the world high tuberculosis (TB) burden countries, pastoralists being the most affected population. However, there is no published report whether the behavior related to TB are different between pastoralist and the sedentary communities. Therefore, the main aim of this study is to assess the pastoralist community knowledge, attitude and perceived stigma towards tuberculosis and their health care seeking behavior in comparison to the neighboring sedentary communities and this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…This could be because of good knowledge in uence attitude formation (30). Furthermore, it was supported by a study from Ethiopia among pastoralist communities which showed lower awareness as risk factors for unfavorable attitudes (34). This could be mainly due to perceiving a higher stigma on TB patients among pastoralists with poor awareness.…”
Section: Discussionmentioning
confidence: 84%
“…This could be because of good knowledge in uence attitude formation (30). Furthermore, it was supported by a study from Ethiopia among pastoralist communities which showed lower awareness as risk factors for unfavorable attitudes (34). This could be mainly due to perceiving a higher stigma on TB patients among pastoralists with poor awareness.…”
Section: Discussionmentioning
confidence: 84%
“…This could be because of good knowledge influence attitude formation [30]. Furthermore, it was supported by a study from Ethiopia among pastoralist communities which showed lower awareness as risk factors for unfavorable attitudes [34]. This could be mainly due to perceiving a higher stigma on TB patients among pastoralists with poor awareness.…”
Section: Discussionmentioning
confidence: 85%
“…5 And this study is also consistent with the study among, pastoralist community, community of Gambella region and Somali community, where participants had higher knowledge gap about tuberculosis. [7][8][9] But, our study contrast with the study among pastoral communities, Ethopia. 10 and study among population of Mamandur in Tami where majority of the participants had adequate knowledge on pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 96%